HIMF (Hypoxia-Induced Mitogenic Factor)-IL (Interleukin)-6 Signaling Mediates Cardiomyocyte-Fibroblast Crosstalk to Promote Cardiac Hypertrophy and Fibrosis. Issue 5 (May 2019) - Kumar, Santosh; Wang, Gang; Zheng, Na; Cheng, Wanwen; Ouyang, Kunfu; Lin, Hairuo; Liao, Yulin; Liu, Jie
Abstract : HIMF (hypoxia-induced mitogenic factor) is a secreted proinflammatory cytokine with a critical role in cardiac hypertrophy development. Loss of HIMF attenuates transverse aortic constriction-induced cardiac hypertrophy and fibrosis, but the underlying mechanisms are unknown. We show that IL (interleukin)-6 production increases following transverse aortic constriction in wild-type mice; this effect is inhibited in HIMF gene knockout ( Himf −/− ) mice. IL-6 production also increases in cultured cardiac myocytes overexpressing HIMF and neutralizing IL-6 with an anti-IL-6 antibody prohibits HIMF-induced cardiomyocyte hypertrophy. HIMF expression in cardiac fibroblasts cannot be stimulated by transverse aortic constriction or exposure to prohypertrophic factors, including phenylephrine, Ang II (angiotensin II), TGF (transform growth factor)-β, and hypoxia. However, conditioned medium from cardiomyocytes overexpressing HIMF can increase IL-6 production, and cardiac fibroblast proliferation, migration, and myofibroblast differentiation to a similar level as exposure to exogenous rHIMF (recombinant HIMF). Again, neutralizing IL-6 prevented cardiac fibroblasts activation. Finally, the MAPK (mitogen-activated protein kinase) and CaMKII (Ca 2+ /calmodulin-dependent protein kinase II)–STAT3 (signal transducers and activators of transcription 3) pathways are activated in HIMF-overexpressing cardiomyocytes and rHIMF-stimulated cardiac fibroblasts; this effect can be inhibited on neutralizing IL-6. These data support that HIMF induces cardiac fibrosis via a cardiomyocyte-to-fibroblast paracrine effect. IL-6 is a downstream signal of HIMF and has a central role in cardiomyocyte hypertrophy and myocardial fibrosis that is mediated by activating the MAPK and CaMKII-STAT3 pathways. Abstract : Supplemental Digital Content is available in the text.